Perceived stress, job satisfaction, and happiness among police personnels posted in offices and fields - Prapti Pradhan; Pratiti Pattnaik; Asmita Nayak (Industrial Psychiatry Journal)
Background: Police personnel are emergency service providers who face many issues in their daily functioning with the public. They expressed subjective stress and tension. In addition, their job’s transitory nature adds to the day-to-day hassles and challenges. However, the services provided by those who are posted in the office and the field are different. Aim: The present study aims to measure and compare the level of stress, job satisfaction, and happiness among police personnel working in the office and field. Materials and Methods: A cross-sectional study was conducted on 60 police personnel from Bhubaneswar and Cuttack cities of Odisha. Three scales were used to assess their stress level, job satisfaction, and happiness: Perceived Stress Scale, Job Satisfaction Scale, and Oxford Happiness Questionnaire. Results: The statistical analysis shows a significant difference between the police personnel posted in the field and office with respect to three variables: perceived stress, job satisfaction, and happiness. Conclusion: The results of the current study underscore the need for ongoing support and mental health services for police personnel, particularly those deployed in the field. It is crucial to address their work’s psychological toll and provide resources to support their mental and emotional well-being.